2016
DOI: 10.1007/s12199-016-0543-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between mass media and body weight concern among Jordanian adolescents’ residents of Amman: the role of gender and obesity

Abstract: Objectives Body image in the mass media promotes an unrealistic picture of body shape that leads to body dissatisfaction among adolescentsQuery. Therefore, the study presented in this paper aimed to assess the association between mass media and adolescents' weight concerns and perceptions of body weight and shape. Methods A cross-sectional survey was conducted on school adolescents aged between 15 and 18 years during the academic year 2013-2014. Multistage stratified sampling method was used. The number of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Similar to findings in other settings, urbanization has been associated with a preference for thinness (Jackson et al, 2003), and research has pointed to the role of sociocultural factors in body image concerns, including the role of media (Tayyem et al, 2016;Saghir and Hyland, 2017) and the internalization of appearance ideals (Melki et al, 2015;Zainal et al, 2020). Perhaps in this geographic area more than others, the role of cultural and religious values and behaviors has been explored, with findings suggesting that the relationships are complex and require further disentangling (Al-Mutawa et al, 2019;Sidi et al, 2020).…”
Section: The Middle Eastmentioning
confidence: 63%
“…Similar to findings in other settings, urbanization has been associated with a preference for thinness (Jackson et al, 2003), and research has pointed to the role of sociocultural factors in body image concerns, including the role of media (Tayyem et al, 2016;Saghir and Hyland, 2017) and the internalization of appearance ideals (Melki et al, 2015;Zainal et al, 2020). Perhaps in this geographic area more than others, the role of cultural and religious values and behaviors has been explored, with findings suggesting that the relationships are complex and require further disentangling (Al-Mutawa et al, 2019;Sidi et al, 2020).…”
Section: The Middle Eastmentioning
confidence: 63%
“…Key indicators of eating disorders were significantly more prevalent among Fijian schoolgirls following prolonged exposure to television 37 . Among Jordanian school adolescents, most students with or without obesity had shown a high impact of reading magazines on their dieting to lose weight 22 . Furthermore, the majority of the American preadolescent and adolescent girls, who enrolled in 5th to 12th grade, were unhappy with their body weight and shape, and this was strongly associated with the frequency of reading fashion magazines 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study showed that such media pressure on female university students from five Arab countries led to a greater risk of dieting to lose weight and changed their ideas of a perfect body shape 21 . A cross-sectional survey that was conducted on Jordanian school adolescents aged 15–18 years found that most adolescents with or without obesity had shown a high impact of reading magazines on their dieting to lose weight 22 . In a sample of 17- to 32-year-old university students from five Arab countries, exposure to television had a weaker association than exposure to magazines regarding females’ body weight concerns 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, the nutritional transition has introduced to Jordanian culture fatty fast food, sweets, high‐calorie drinks, and salt which have led to increasing rates of overweight and obesity. At the same time, adolescents are being exposed to the unrealistic ideal of slim beauty that is portrayed in the media and by various advertising industries offering products to lose weight (Mousa, Mashal, et al, ; Tayyem et al, ). This paradox may contribute to escalating rates of dissatisfaction with body image, unhealthy eating behaviours, and DE.…”
Section: Discussionmentioning
confidence: 99%
“…Jordanian adolescents are increasingly affected by Western culture in two ways: first in the change in lifestyle (eg, eating fast foods) and secondly in accepting thinness as beautiful. This may be the cause of the increase in obesity and dieting among adolescents, leading to an increase in reported cases of DE (Madanat, Brown, & Hawks, 2007;Madanat, Lindsay, & Campbell, 2011;Tayyem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%